Herpes Simplex Virus 1 Envelope Cholesterol Facilitates Membrane Fusion - Wudiri, George A.; Schneider, Seth M.; Nicola, Anthony V. (Frontiers in Microbiology, 2017)
Methyl beta-cyclodextrin (MβCD) treatment of herpes simplex virus 1 (HSV-1) reduced envelope cholesterol levels and inhibited viral entry and infectivity in several cell types, regardless of the dependence of entry on endocytosis or low pH. Viral protein composition was similar in MβCD-treated and untreated virions, and ultrastructural analysis by electron microscopy revealed that cholesterol removal did not grossly affect virion structure or integrity. Removal of envelope cholesterol greatly reduced virion fusion activity as measured by fusion-from-without, suggesting that virion cholesterol is critical for the step of membrane fusion. MβCD-treatment of HSV-1 did not reduce viral attachment to the cells nor endocytic uptake of HSV-1 from the cell surface. The pre-fusion form of gB present in the HSV-1 envelope undergoes conformational changes in response to mildly acidic pH. These gB changes occurred independently of envelope cholesterol. Removal of cholesterol compromised virion stability as measured by recovery of infectivity following cycles of freeze-thaw. Taken together, the data suggest that HSV-1 envelope cholesterol is important for viral entry and infectivity due to a critical role in membrane fusion.